Follow-up programs for childhood cancer survivors in Europe: a questionnaire survey. - Stefan Essig (Public Library of Science (PLoS), 2012)
Background For many childhood cancer survivors follow-up care is important long after treatment completion. We aimed to describe the availability and characteristics of long-term follow-up programs (LTFU) across Europe, their content and aims, their problems, and to assess opinions on different models of LTFU. Methodology/principal findings We asked 179 pediatric oncology institutions in 20 European countries to complete an online survey on LTFU available at their institution. Of 110 respondents (62% response), 66% reported having LTFU for pediatric survivors, 38% for adult survivors of childhood cancer. Availability varied widely across European regions, from 9% of institutions in Northern Europe reporting LTFU for adult survivors to 83% of institution on the British Isles reporting LTFU for pediatric survivors. Pediatric and adult LTFU were usually located in pediatric hospitals and run by pediatric oncologists. Content of follow-up included screening for adverse outcomes and health education. Important problems included lack of time, personnel and funding. Most institutions without LTFU reported that they would like to offer a program (86%). Conclusion/significance Despite general agreement on the need of follow-up care, there is still a lack of well-organized LTFU for survivors of childhood cancer across Europe.